2021
DOI: 10.3390/polym13152500
|View full text |Cite
|
Sign up to set email alerts
|

Bending and Shear Behaviour of Waste Rubber Concrete-Filled FRP Tubes with External Flanges

Abstract: An innovative beam concept made from hollow FRP tube with external flanges and filled with crumbed rubber concrete was investigated with respect to bending and shear. The performance of the rubberised-concrete-filled specimens was then compared with hollow and normal-concrete-filled tubes. A comparison between flanged and non-flanged hollow and concrete-filled tubes was also implemented. Moreover, finite element simulation was conducted to predict the fundamental behaviour of the beams. The results showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The results defined the R 2 value equals to 0.86. The developed equation is provided below: f cu = 0.0554ρ − 100.55; R 2 = 0.70; Adjusted R 2 = 0.69 (1) where,…”
Section: Correlationships Between Density Thermal and Mechanical Prop...mentioning
confidence: 99%
See 1 more Smart Citation
“…The results defined the R 2 value equals to 0.86. The developed equation is provided below: f cu = 0.0554ρ − 100.55; R 2 = 0.70; Adjusted R 2 = 0.69 (1) where,…”
Section: Correlationships Between Density Thermal and Mechanical Prop...mentioning
confidence: 99%
“…The properties of rubberised concrete are affected by the parameters of rubber particles, namely rubber content, rubber particle size, and surface conditions of rubber particles. The mechanical properties of rubberised concrete are negatively affected as the content of rubber particles increases [1][2][3], attributed to the poor bonding between rubber particles and the cement matrix and the low stiffness of rubber.…”
Section: Introductionmentioning
confidence: 99%
“…The accuracy of the stress-strain model can be judged by comparing the predicted curves with the test curves. The specific operation is to substitute the theoretical values of peak stress f cc , peak strain ε cc , ultimate stress f cu and ultimate strain ε cu of confined concrete columns into Equations (10) and (11) to determine the values of parameters a and c, thus obtaining the predicted stress-strain relationship curves of confined concrete column specimens in this database. Figure 14 compares the model prediction curve with the actual test curve of partially stirrup-only confined concrete columns studied by this test and others in the database.…”
Section: Model Performancementioning
confidence: 99%
“…At present, the research on the mechanical properties of FRP-confined concrete has been very sufficient. Research mainly focuses on the axial compression or eccentric compression properties of FRP-confined concrete [3][4][5][6][7][8][9], and some novel research, such as Wahid Ferdous et al [10], studied the bending and shear behaviour of waste rubber concrete-filled FRP tubes with external flanges. In addition, FRP can also be made into FRP reinforcement with superior environmental and mechanical properties to replace ordinary reinforcement.…”
Section: Introductionmentioning
confidence: 99%
“…The current traditional methods for waste concrete are landfills or littered in the open, which not only occupies large amounts of land but also causes the waste of resources. Many scholars at home and abroad have used crushed and graded waste concrete to replace natural coarse aggregate (NCA) to prepare recycled aggregate concrete (RAC) [2][3][4]. It was found that recycled coarse aggregate (RCA) had the characteristic features of lower tensile strength, weak interfacial zone (ITZ), and higher porosity compared with NCA [5][6][7], which limited the practical engineering applications of RAC.…”
Section: Introductionmentioning
confidence: 99%